Hamlet. - Shakespeare, William, 1564-1616.; Shakespeare, William, 1564-1616. (New York : SparkNotes, 2003)
Presents the full text of Shakespeare's "Hamlet", with side-by-side translations on facing pages to help readers better understand the play, as well as critical commentary.
Young Adult.
Young Adult
Keywords: English literature -- History and criticism -- Juvenile literature; Fathers -- Death -- Juvenile drama; Hamlet (Legendary character) -- Juvenile drama; Murder victims' families -- Juvenile drama; Princes -- Juvenile drama; Revenge -- Juvenile drama; English literature -- History and criticism; Fathers -- Death -- Drama; Hamlet (Legendary character) -- Drama; Murder victims' families -- Drama; Princes -- Drama; Revenge -- Drama; English literature -- History and criticism; Fathers -- Death -- Drama; Hamlet (Legendary character) -- Drama; Princes -- Drama; Revenge -- Drama; Tragedies; Victims of crimes -- Drama; Denmark -- Juvenile drama; Denmark -- Drama; Denmark -- Drama; Tragedies